Grain grinding size of cereals in complete pelleted diets for growing lambs: Effects on ruminal microbiota and fermentation - Andres, Sonia (2018)
Lambs from intensive dairy sheep production systems are sold out either after weaning as milk-fed lambs or after a fattening characterized by high intakes of concentrate feeds (mainly cereals) which can lead to ruminal disorders. Therefore, it is essential to explore different feeding alternatives in order to reach a balance between economic or productive benefits and animal welfare. Twenty weaned male lambs (6–8 weeks age, 14.8 ± 0.16 kg body weight) were allocated randomly to one of two different groups (n=10 per group) to study the effect of feeding a complete pelleted diet (CPD) in which cereal grains were ground at two different sieve sizes (either 2-mm with 13.5% dry matter (DM) of the particles>1.7mm or 6-mm with 47.1% DM of particles>1.7 mm) on DM intake, nutrient digestibility, ruminal microbiota and fermentation. Lambs were fed the corresponding CPD ad libitum and slaughtered when they reached 27 kg. DM intake was greater in the lambs fed 2-mm grains than in those fed 6-mm grains (P < .05). Feeding 2-mm grains in comparison to 6-mm grains resulted in darker colour of ruminal mucosa (100 vs. 127, from a scale where 0 is black and 256 white; SED=9.8; P=.017) and thicker stratum corneum (45.3 vs. 30.9 μm; SED=3.67; P=.001), suggesting more severe acidotic conditions in the rumen with the smaller cereal particle size. Analysis of microbial communities revealed that the presence of ruminal bacteria such as Prevotella and Quinella was increased in the digesta of animals fed the 2-mm diet. These data were corroborated by the odd- and branched-chain fatty acid profile of ruminal contents, which would indicate a shift from cellulolytic to amylolytic bacteria in the rumen of lambs fed the 2-mm diet. In conclusion, feeding 6-mm in comparison to 2-mm ground cereal grains included in CPD formulated for growing lambs is an alternative strategy that may reduce ruminal acidosis through changes in the microbiota.w